2008
DOI: 10.1111/j.1471-4159.2008.05548.x
|View full text |Cite
|
Sign up to set email alerts
|

Native cone photoreceptor cyclic nucleotide‐gated channel is a heterotetrameric complex comprising both CNGA3 and CNGB3: a study using the cone‐dominant retina of Nrl−/− mice

Abstract: Cone vision mediated by photoreceptor cyclic nucleotide‐gated (CNG) channel activation is essential for central and color vision and visual acuity. Mutations in genes encoding the cone CNG channel subunits, CNGA3 and CNGB3, have been linked to various forms of achromatopsia and progressive cone dystrophy in humans. This study investigates the biochemical components of native cone CNG channels, using the cone‐dominant retina in mice deficient in the transcription factor neural retina leucine zipper (Nrl). Abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 75 publications
(225 reference statements)
2
47
0
Order By: Relevance
“…8 E-G) (Ding and Weinberg, 2007), it is unclear how this could affect cone [Ca 2ϩ ]. Inconsistent with a major role for the NO-sGC-cGMP pathway in mammalian cones are also the facts that CNG channels could not be detected in cone terminals (Matveev et al, 2008) and that we failed to detect NOS activity in the outer retina.…”
Section: Cone Terminal [Ca 2؉mentioning
confidence: 68%
“…8 E-G) (Ding and Weinberg, 2007), it is unclear how this could affect cone [Ca 2ϩ ]. Inconsistent with a major role for the NO-sGC-cGMP pathway in mammalian cones are also the facts that CNG channels could not be detected in cone terminals (Matveev et al, 2008) and that we failed to detect NOS activity in the outer retina.…”
Section: Cone Terminal [Ca 2؉mentioning
confidence: 68%
“…Nevertheless, as a unique mammalian cone-dominant model, the Nrl Ϫ/Ϫ mouse line has been widely used for the study of cone biology and disease (26,38,39). We have previously shown that the retinas of Nrl Ϫ/Ϫ mice express an abundant amount of cone CNG channel and lack the expression of the rod channel (25). In this study, we show that the double knock-out mice showed a retinal phenotype similar to that in their respective single knock-out mice, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal Protein Sample Preparation, SDS-PAGE, and Western Blot Analysis-Retinal protein sample preparation, SDS-PAGE, and Western blotting were performed as described previously (25). Briefly, retinas were homogenized in homogenization buffer (20 mM HEPES-NaOH, pH 7.4, 1 mM EDTA, 200 mM sucrose, containing protease mixture (Sigma)).…”
Section: Mice Antibodies and Other Materials-the Cnga3mentioning
confidence: 99%
“…Mouse mAB against GFAP was purchased from Chemicon International (MAB302, Temecula, CA, USA) and was used at 1 : 1000 for IF. Rabbit polyclonal antibody against the b-subunit of the cone cyclic nucleotide-gated channel (CNGB3) was generously shared by Dr Xi-Qin Ding (University of Oklahoma Health Sciences Center) (46,47) and was used at 1 : 250 for IF. Rabbit polyclonal antibody against cone transducin (GNAT2, 1 : 1000 IF) was purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA) (10) as was goat polyclonal antibody against S-opsin (1 : 500 IF).…”
Section: Antibodiesmentioning
confidence: 99%